Pricing the Transfer of Intellectual Property as a Problem of Second-Best Tax Policy - Wolfram F. Richter; Markus Breuer (Center for Economic Studies and ifo Institute (CESifo), 2015)
The adequate pricing of intellectual property (“IP”) for tax reporting is a largely unsettled issue. Transactional profit-based methods are on the rise although only rated as “methods of last resort” by the OECD. This paper focuses on regulated profit splitting and compares this transfer pricing rule with one allowing multinationals to price IP freely subject to the constraint that the price used for tax reporting is also used internally. The standard of comparison is global efficiency in R&D. The model is one of second best. It allows for internationally differentiated tax rates and non-deductible effort costs in the production of know-how.
Keywords: H25; O34; M48; F23; 330; transfer pricing rule; intellectual property; profit split method; allocational efficiency; second-best policy